Challenges and future directions of biocomposite materials - Lelly, Marini; Mohammad, Abdul Mannan; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Woodhead Publishing / Elsevier Ltd., 2026)
Biocomposites, made from natural fibers and bio-based or synthetic matrices, are gaining attention as eco-friendly alternatives due to rising environmental concerns and strict emissions regulations. Their growing use in various industries highlights their potential for sustainability. Biocomposites face challenges in material consistency, mechanical strength, and scalability, limiting their industrial adoption. The research problem is that achieving ultra-high-strength in biocomposites while maintaining reduced weight is challenging due to material composition limitations. Optimizing the Si/Al ratio and enhancing SiO₂ and Al₂O₃ content are key to improving performance. This study optimizes the Si/Al ratio and increases SiO₂ and Al₂O₃ content to enhance strength while reducing weight. Mechanical tests (compressive, flexural) and microstructural analyses [scanning electron microscopy (SEM)–energy dispersive spectroscopy (EDS), fourier transform infrared spectroscopy (FTIR)] will evaluate these effects, while machine learning models (ANN, XGB, MLR) will optimize the mix design and validate predictions. Ultra-high-strength lightweight geopolymer concrete achieved high strength (122.9–168.8MPa) with a cost-effective mix. The XGB model performed best (mean squared error: 139.41, R²: 0.938), with predicted strengths 18%–22% above experimental results. Flexural strength reached 22.2 MPa (71% increase) with a 25% waterglass reduction. SEM–EDS showed improved adhesion, and FTIR confirmed enhanced geopolymer networks. A density of 1.704 g/cm³ balances strength and lightweight properties. Costs ranged from RM 71,608.7 to RM 72,134.7/m3, with lower CO₂ emissions and reduced raw material use.